UI DESIGN APLIKASI MOBILE E-TIKET PT.NPM - Yoga Kurnia putra; dini faisal (DEKAVE : Jurnal Desain Komunikasi Visual, 2020)
Designing UI Design mobile Application e-ticket PT. NPM aims to increase the promotion, quality and user transportation of the company PT. NPM. This app is expected to assist in carrying out a ticket purchase transaction which can be used by any person anywhere and anytime. The glass box method is a logical and rational thinking method used in designing the UI Design of PT. E-Ticket mobile application. NPM. This NPM Mobile app is designed with a good UI with a nice layout, so users are comfortable and the application is usable when used. The NPM Mobile app has the main content, i.e. ticket messages and supporting content i.e., deals, points, vouchers and refunds. The content is well organized and neatly grouped, so users easily know the information needed. The process of problem solving, SWOT analysis is used (Strenght, Weakness, Opportunity, Threat) to find the solution of the problems encountered. To get information, observe and interview the user's head. Author eligibility tests do to some samples to determine deserving and usable in the application that the author designed. In the results of the first feasibility test almost all samples say less satisfied with the appearance of the application, which related to the layout is still messy, the font size Kuran pas and navigation buttons too small. The author further repairs and performs a second feasibility test. The result of this agility test is satisfactory, the sample says very fond of the entire look of the application. So this NPM Mobile app UI is already decent and useble used. To support major media, made supporting media, motion graphic, x-banner, poster, T-shirt, Totebag, keychains and sticker.Keyword : Mobile application, bis transportation, user interface